2019
DOI: 10.1186/s12879-019-4529-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of the cause of decreased blood 1,25-Dihydroxyvitamin D in sepsis

Abstract: BackgroundVitamin D deficiency, determined by blood levels of 25-hydroxyvitamin D [25(OH) D, i.e. the major vitamin D form in blood], has been shown to associate with all-cause mortalities. We recently demonstrated that blood levels of 1,25-dihydroxyvitamin D [1,25(OH)2D, i.e. the active vitamin D] were significantly lower in non-survivors compared to survivors among sepsis patients. Unexpectedly, despite the well documented roles of 1,25(OH)2D in multiple biological functions such as regulation of immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Additionally, we recently demonstrated that serum levels of 1,25(OH) 2 D 3 were significantly lower in non-survivors compared to survivors among sepsis patients, and that complex mechanisms underlie low 1,25(OH) 2 D 3 in critically ill patients [27].…”
Section: Yin and Yang Of Vitamin D Applicationmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, we recently demonstrated that serum levels of 1,25(OH) 2 D 3 were significantly lower in non-survivors compared to survivors among sepsis patients, and that complex mechanisms underlie low 1,25(OH) 2 D 3 in critically ill patients [27].…”
Section: Yin and Yang Of Vitamin D Applicationmentioning
confidence: 98%
“…Vitamin D sufficiency is widely defined as a serum 25-hydroxyvitamin D (25(OH)D) level greater than or equal to 30 ng/ ml (75 nmol/L), while insufficiency is defined as 20 to 30 ng/ml (50-75 nmol/L), and deficiency is a level lower than 20 ng/ml (50 nmol/L) [25]. A low level of vitamin D is common in the elderly and has been associated with all-cause mortality including sepsis, and that supplementation of vitamin D could significantly reduce overall mortality [26,27]. Besides geographic and climate factors, vitamin D deficiency is also more prevalent among individuals with darker skin than those with a lighter skin color due to the fact that heavy pigmentation reduces vitamin D production in the skin [28].…”
Section: Introductionmentioning
confidence: 99%
“…To treat LPS-induced ALI, we elected to utilize the following two therapeutic agents: insulin-like growth factor-I (IGF-I) and the store-operated calcium channel inhibitor (BTP-2). IGF-I therapy was selected, because we observed a reduction in the serum IGF-I in our past sepsis studies [ 9 ]. Previously, we found that the decrease in serum IGF-I during sepsis was associated with the depression of growth hormone receptor (GHR) expression in the liver and increased circulating inflammatory cytokines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-I therapy was selected, because we observed a reduction in the serum IGF-I in our past sepsis studies [ 9 ]. Previously, we found that the decrease in serum IGF-I during sepsis was associated with the depression of growth hormone receptor (GHR) expression in the liver and increased circulating inflammatory cytokines [ 9 ]. Since inflammatory cytokines were known to suppress GHR expression in the liver, which was the primary source of circulating IGF-I, we reasoned that the suppressed liver GHR expression accounted for the low-serum IGF-I under systemic inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a possible hypothesis that could explain our findings would be that tissue damage in the kidneys and to a lesser extent in the lung caused by SARS-CoV2 may lead to an active decrease of 1,25(OH)D, responsible for the majority of biological actions of Vitamin D, but not in the form usually determined in plasma, Calcifediol. Previous studies showed that blood 25(OH)D levels may not correlate with blood 1,25(OH) 2 D levels in some clinical conditions [6365].…”
Section: Discussionmentioning
confidence: 99%